Rubus ulmifolius Schott fruits: A detailed study of its nutritional, chemical and bioactive properties - Silva, Liliana Primo da (2018)
The authors are grateful to the Foundation for Science and Technology (FCT, Portugal) and FEDER under Program PT2020 for financial support to CIMO (UID/AGR/00690/2013), L. Barros and R. Calhelha contracts. The authors are also grateful to the Interreg España- Portugal for financial support through the project 0377_Iberphenol_6_E). This work is also funded by the European Structural and Investment Funds (FEEI) through the Regional Operational Program North 2020, within the scope of Project NORTE- 01-0145-FEDER-023289: DeCodE and project Mobilizador Norte-01- 0247-FEDER-024479: ValorNatural®. The authors also thank Professor of Botany Carlos Aguiar for the help given for the plant material collection and botanical identification.